Nitrogen redistribution to sorghum grains as affected by plant competition - Rosolem, Ciro Antonio [UNESP]; Kato, S. M.; Machado, J. R.; Bicudo, Silvio José [UNESP] (Springer, 1993)
An experiment was conducted to study nitrogen absorption and translocation in grain sorghum plants during their reproductive growth. Sorghum was grown in four row spacings: 50 and 70 cm in single rows, 80 and 120 cm in double rows 20 cm apart. Plant populations were 71000, 142000 and 213000 plants/ha. After flowering, samples were taken at 12 day intervals, and the plants were divided into grains and stover, where N was analyzed. There was an increase in N concentration in lower plant populations and in wider row spacings. However, total nitrogen accumulation (in kg/ha) increased as the number of plants was increased. In the vegetative parts of the plants there were higher N concentrations in lower populations showing that there was a higher N absorption and a lower translocation to the grains. When grain sorghum was grown in 50 cm rows, there was a high N accumulation, a high N translocation to the grains and the highest yield. This row spacing led to the highest N use efficiency.
Keywords: Nitrogen partitioning; Plant competition; Planting Pattern; Population; Sorghum bicolor